How do you solve using gaussian elimination or gauss-jordan elimination, 2x-y+z=62xy+z=6, x+2y-z=1x+2yz=1, 2x-y-z=02xyz=0?

1 Answer
Dec 13, 2015

Set up an augmented matrix and row-reduce to find
{(x = 2),(y=1),(z=3):}

Explanation:

Using Gaussian Elimination on the given system, we start from

{(2x-y+z=6),(x+2y-z=1),(2x-y-z=0):}

and use the system to set up the augmented matrix

((2,-1,1,|,6),(1,2,-1,|,1),(2,-1,-1,|,0))

Our goal is a matrix of the form

((1,0,0,|,x),(0,1,0,|,y),(0,0,1,|,z))

Note that from here, we may use only the following operations:

  • multiply a row by a constant

  • add a the product of a row and a constant to another row

  • switch the positions of two rows

To obtain a 1 in the first row, first column, we multiply the first row by 1/2 and obtain

((1,-1/2,1/2,|,3),(1,2,-1,|,1),(2,-1,-1,|,0))

To obtain 0s for the remainder of the first column, we add -1 times the first row to the second row, and -2 times the first row to the third row.

((1,-1/2,1/2,|,3),(0,5/2,-3/2,|,-2),(0,0,-2,|,-6))

We could solve for z and use back-substitution at this point, but let's proceed with Gauss-Jordan elimination. The next step is to get a 1 in the second row, second column. To do so, we multiply the second row by 2/5.

((1,-1/2,1/2,|,3),(0,1,-3/5,|,-4/5),(0,0,-2,|,-6))

Again, we want 0s for every other member of the column. To get this, we add 1/2 times the second row to the first row.

((1,0,1/5,|,13/5),(0,1,-3/5,|,-4/5),(0,0,-2,|,-6))

As our next to last step, we want a 1 in the third column, third row. To obtain this, we multiply the third row by -1/2.

((1,0,1/5,|,13/5),(0,1,-3/5,|,-4/5),(0,0,1,|,3))

Finally, we eliminate the remaining nonzero elements of the third column by adding -1/5 times the third row to the first row, and 3/5 times the third row to the second row.

((1,0,0,|,2),(0,1,0,|,1),(0,0,1,|,3))

And so we have

{(x = 2),(y=1),(z=3):}